Career Guidance to Improve the Future Orientation of Elementary School Students - Tita Rosita; Mutiara Tectonia Safitri (Jurnal Counseling Care, 2024)
This research aims to determine the level of understanding of elementary school students' future orientation. The research method used is quasi-experimental with a one-group before-after design. The sample in this research was 14 grade 6 elementary school students. Based on the research results, it show that the future orientation of Al-Irhaam Elementary School students increased after receiving career guidance services for two sessions. Thus, career guidance is effective in providing an understanding of students' future orientation in the aspects of motivation, planning, and evaluation. The motivation stage includes motives, interests, and goals related to future orientation; the planning stage is related to determining goals, preparing plans, and implementing plans; and the evaluation stage includes the stage where students assess the behavior displayed, as well as provide reinforcement from themselves.